2016
DOI: 10.1007/978-3-662-53174-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Open Problems on Graph Coloring for Special Graph Classes

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…We remark that an extended version of this article, which includes a survey on computational complexity results for graph classes defined by some other forbidden pattern, is available . For a survey on computational complexity results and open problems for coloring graphs characterized by more than two forbidden induced subgraphs or for which some graph parameter is bounded, see .…”
Section: Introductionmentioning
confidence: 99%
“…We remark that an extended version of this article, which includes a survey on computational complexity results for graph classes defined by some other forbidden pattern, is available . For a survey on computational complexity results and open problems for coloring graphs characterized by more than two forbidden induced subgraphs or for which some graph parameter is bounded, see .…”
Section: Introductionmentioning
confidence: 99%
“…The coloring problems investigated in this article are formally defined below, adopting the notation from other papers; see e.g. [32]. In each of the problems defined below, we consider k to be a fixed integer with k 1.…”
Section: Definitions and Notationmentioning
confidence: 99%
“…A long-standing and still open question about coloring problems is whether one can decide in polynomial time if a graph with diameter two can be properly colored using at most three colors (see e.g. [22,32]), and only recently the answer for the 3-Coloring problem on graphs with diameter at most three has been settled negatively by Mertzios and Spirakis [30]. Here we propose the investigation of analogous questions concerning list colorings of bipartite graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The first two problems we study are the following ones stated by Golovach et al [19] (see also [24]) who asked to determine their parameterized complexity. These questions were motivated by a result of Cai [8] who showed that Coloring Clique Modulator (the special case of Pre-Coloring Extension Clique Modulator when X = ∅) is fixed-parameter tractable (FPT).…”
Section: Introductionmentioning
confidence: 99%